Comparison of mechanical complications of central venous catheter according to the insertion site in an intensive care unit of Bangladesh (BIRDEM Medical Journal, 2020)
Background: Central venous catheter (CVC) insertion is very common in intensive care unit (ICU). CVC is usually inserted in subclavian, internal jugular and femoral veins. However, CVC insertion may lead to significant mechanical complications. Our aim was to detect the occurrence of CVC related mechanical complications according to different insertion site.Methods: This prospective observational study was carried out during the period of May 2016 to July 2019 in Department of Critical Care Medicine, BIRDEM General Hospital, Dhaka, enrolling 349 adult patients requiring new CVC insertion in ICU.Results: Among 349 study subjects, 167 CVC were inserted through subclavian vein, 88 through internal jugular and 94 through femoral vein. There was no significant difference among three groups (subclavian / internal jugular / femoral) in terms of age, gender distribution, presence of co-morbid illness.Total mechanical complicationsin study population was 43 (12.3 %) including pneumothorax (14, 4.0%), arterial puncture (10, 2.9%), hemorrhage (11, 3.2%), catheter tip malposition (6, 1.7%), hemothorax (1, 0.3%) and lost guidewire (1, 0.3%). Pneumothorax was more with internal jugular (9.1%) than subclavian (3.6 %) route, which was statistically significant (p=0.007). Although hemorrhage and arterial puncture events were higher with femoral site than subclavian or internal jugular, which were not significant. Catheter tip malposition occurred in 4 (2.4%) patients with subclavian insertion and 2 (2.3%) patients with internal jugular site, no such event in femoral site. Hemothorax and lost guidewire occurred in only 1 patient with subclavian and internal jugular site respectively. Site-wise total mechanical complications were higher in internal jugular (17.0%) followed bysubclavian (10.8%) site and femoral site (10.6%).Conclusion: In this study, though not statistically significant, CVC related mechanical complications occurred more in subclavian site than in internal jugular or femoral insertion site.Birdem Med J 2020; 10(2): 115-119